Relationship between Health Belief Model constructs and smoking behavior among school-age adolescents in Indonesia: A cross-sectional study - Vionalita, Gisely; Kusumaningtiar, Devi Angeliana; Angkasa , Dudung (Public Health of Indonesia, 2023)
Background: Programs aimed at altering health risk behavior in adolescents have frequently been a priority for the health department in Indonesia. However, these efforts have not yielded optimal results thus far. The Health Belief Model (HBM) is considered a dependable indicator for predicting health-risk behavior. Objective: This study sought to establish the relationship between the constructs of the Health Belief Model (HBM) – namely, perceived susceptibility to health-related issues due to smoking, perceived barriers to non-smoking, perceived benefits of non-smoking, perceived self-efficacy to non-smoking, and cues to action for non-smoking – and smoking behavior among adolescents of school age. Methods: The study employed a cross-sectional design, examining smoking behavior in 171 school-age adolescents in Indonesia. This was done using an online Indonesian Smoking Behavior Questionnaire and a validated Indonesia Health Belief Model Questionnaire that measures the five domains of HBM. The Chi-square test was utilized to explore associations among different variables. Results: Adolescents with an average age of 16.04 years (ranging from 12 to 17 years) reported a 5.8% incidence of smoking in the past 30 days. Significantly, there was a relationship between perceived susceptibility (p = 0.002), barriers to quitting smoking (p <0.001), cues to action (p = 0.019), and smoking behavior in adolescents. Conclusion: The study provides valuable insights into how the Health Belief Model is linked to the involvement of adolescents in health risk behavior, particularly smoking. This information is crucial for the development of health education tailored to adolescents of school age.